Ethnobotany, Phytochemistry, Pharmacology, and Toxicology of Cycas revoluta Thunb.: An Updated Review - K, Abdul Jaleel; PS, Prakash; KV, Nakshathra; V, Devika (Sciences of Phytochemistry, 2026)
Cycas revoluta Thunb. (sago palm), a cycad native to southern Japan, is widely cultivated and has a long history of ethnobotanical use, including as a famine food and in traditional medicine, but is also well known for its pronounced toxicity to humans and animals. This review critically synthesizes literature published between 1958–2025 on the ethnobotany, phytochemistry, pharmacology, and toxicology of C. revoluta from ScienceDirect, PubMed, Scopus, and Google Scholar. Presented as a structured narrative review, the study highlights diverse phytochemicals, including biflavonoids, cycasin, β-N-methylamino-L-alanine (BMAA), and reported antimicrobial peptides, noting variability in compound verification and reproducibility. Reported pharmacological activities are derived mainly from in vitro and preclinical studies, with limited in vivo validation and no established clinical relevance, whereas toxicological evidence for neurotoxicity, genotoxicity, and hepatotoxicity is robust. This imbalance underscores the need for caution in extrapolating therapeutic potential. Key gaps include inadequate extract standardization, limited bioavailability and safety data, and overreliance on single-study findings. Future research should prioritize rigorous toxicological assessment and reproducible validation before any translational application is considered. In addition, the review emphasizes the importance of distinguishing traditional knowledge from experimentally validated evidence and separating descriptive phytochemical inventories from mechanistic and translational insights. Particular attention is given to methodological limitations, including inconsistent extraction protocols, insufficient structural confirmation of reported compounds, and the frequent absence of dose–response, pharmacokinetic, and long-term safety evaluations. By adopting a critical and balanced perspective, this review aims to guide future studies toward scientifically rigorous, ethically responsible, and clinically relevant research directions.